SFPQ Promotes Lung Cancer Malignancy via Regulation of CD44 v6 Expression - Yang, Libang; Yang, Jianbo; Jacobson, Blake; Gilbertsen, Adam; Smith, Karen; Higgins, LeeAnn; Guerrero, Candace; Xia, Hong; Henke, Craig A.; Lin, Jizhen (Frontiers in Oncology, 2022)
Mesenchymal stem cells (MSCs) contribute to tumor pathogenesis and eliciting antitumor immune responses in tumor microenvironments. Nuclear proteins might be the main players in these processes. In the current studies, combining spatial proteomics with Ingenuity pathway analysis (IPA) in lung Non-small cell (NSC) cancer MSCs, we identify a key nuclear protein regulator, SFPQ (Splicing Factor Proline and Glutamine Rich), is overexpressed in lung cancer MSCs, and functions to promote MSCs proliferation, chemical resistance, and invasion. Mechanistically, knockdown of SFPQ reduces CD44v6 expression to inhibit lung cancer MSCs stemness, proliferation in vitro, and metastasis in vivo. The data indicates that SFPQ may be a potential therapeutic target for limiting growth, chemotherapy resistant and metastasis of lung cancer.